Comment on Rauchman et al. Mild-to-Moderate Traumatic Brain Injury: A Review with Focus on the Visual System. Neurol. Int. 2022, 14, 453-470 - Nir Erdinest; Naomi London (MDPI AG, 2022)
This letter is regarding the article, "Mild-to-Moderate Traumatic Brain Injury: A Review with Focus on the Visual System" [...]